2014
DOI: 10.1017/s1368980014001554
|View full text |Cite
|
Sign up to set email alerts
|

Predicted efficacy of the Palestinian wheat flour fortification programme: complementary analysis of biochemical and dietary data

Abstract: Objective: To utilize complementary biochemical and dietary data collected before the initiation of national flour fortification to (i) identify micronutrient insufficiencies or deficiencies and dietary inadequacies in Palestinian women and children in vulnerable communities and (ii) assess the suitability of the current wheat flour fortification formula. Design: Quantitative dietary intake questionnaires were administered and fasting venous blood samples collected in randomly selected households in Gaza City … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
(30 reference statements)
4
8
0
Order By: Relevance
“…The present data showed vitamin D deficiency to be common among Palestinian postmenopausal women which is consistent with the widespread vitamin D deficiency in Palestine [ 39 ] and Middle Eastern Arab countries [ 15 , 27 , 40 ]. The level of vitamin D depends on several factors including diet, exposure to sun, age, feeding habits, life style, metabolic, genetic, and other environmental factors [ 7 , 41 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The present data showed vitamin D deficiency to be common among Palestinian postmenopausal women which is consistent with the widespread vitamin D deficiency in Palestine [ 39 ] and Middle Eastern Arab countries [ 15 , 27 , 40 ]. The level of vitamin D depends on several factors including diet, exposure to sun, age, feeding habits, life style, metabolic, genetic, and other environmental factors [ 7 , 41 ].…”
Section: Discussionsupporting
confidence: 88%
“…Table 2 showed that 14.1% of the study subjects had severe vitamin D deficiency (< 10 ng/ml 25(OH)D with mean ± SD 8.51 ± 1.28 ng/ml), whereas 71.8% had vitamin D insufficiency or borderline [25(OH)D 10 to < 20 ng/ml with mean ± SD 13.26 ± 2.20 ng/ml]. Subjects with normal (vitamin D sufficient) represented 14.1% [25(OH)D ≥ 20 ng/ml with mean ± SD 24.55 ± 3.60 ng/ml] [ 7 , 39 ]. Chi-square analysis showed no statistically significant difference in the prevalence of vitamin D groups between osteoporosis and control subjects.…”
Section: Resultsmentioning
confidence: 99%
“…The evidence suggests that the State of Palestine has a higher prevalence of vitamin A and D deficiencies than some of its neighboring countries. Vitamin A deficiency was found in 73.1% of children, which is similar to the 76% prevalence rate found in two previous cross-sectional studies in the State [ 14 , 24 ], however, it is much larger than the 15% to 40% range observed in Southern Israel, Turkey and Iran [ 16 , 20 , 21 , 25 ]. As for vitamin D, 60.7% of children were deficient, which falls in the upper end of the range of deficiency reported by Bassil et al in a systematic review of VDD in the Middle East and North Africa (30–75%) [ 3 ].…”
Section: Discussionsupporting
confidence: 84%
“…This is often due to the high costs of data collection and analysis. In fact, few countries-with a few notable exceptions such as Cameroon [25,26] and Palestine [27]-have used recent dietary intake and micronutrient deficiency data to inform the design of food fortification programs, including the selection of foods and setting of national standards. Consequently, some fortification programs have selected food vehicles that are not widely consumed in a fortifiable form [9] and/or set standards that are not aligned with the consumption patterns and the nutritional needs of the population [28].…”
Section: Quality Coverage and The Potential For Impact Of Lsff Progmentioning
confidence: 99%